2022
DOI: 10.1016/j.ab.2020.113894
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in aptamer applications for analytical biochemistry

Abstract: Aptamers are typically defined as relatively short (20–60 nucleotides) single-stranded DNA or RNA molecules that bind with high affinity and specificity to various types of targets. Aptamers are frequently referred to as “synthetic antibodies” but are easier to obtain, less expensive to produce, and in several ways more versatile than antibodies. The beginnings of aptamers date back to 1990, and since then there has been a continual increase in aptamer publications. The intent of the present account was to foc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 148 publications
(176 reference statements)
0
12
0
Order By: Relevance
“…Once the complex of aptamer and viral protein is formed, antibodies are added to it. This Ag-Ab complex is detected using an anti-antibody labeled with the fluorescence probe and observed under the fluorescent microscope (Zon, 2020). Being a nanodevice, this technique is very sensitive and a very small sample volume is needed, but it requires a sophisticated instrument for assay, which is its main drawback.…”
Section: Nanoarray Aptamer Chip Assaymentioning
confidence: 99%
“…Once the complex of aptamer and viral protein is formed, antibodies are added to it. This Ag-Ab complex is detected using an anti-antibody labeled with the fluorescence probe and observed under the fluorescent microscope (Zon, 2020). Being a nanodevice, this technique is very sensitive and a very small sample volume is needed, but it requires a sophisticated instrument for assay, which is its main drawback.…”
Section: Nanoarray Aptamer Chip Assaymentioning
confidence: 99%
“…This results in the shift of fluorescence emission from one fluorophore to the other and thereby change in the fluorescence color. 244 The first assay using MABs was done to detect the Tat protein of HIV-1. The study reported that the advantage of using MABs was that these require half the length of target sequence, that is, just 8 nucleotides in comparison to the general molecular beacons.…”
Section: Conclusion: Future Outlook and Roadmapmentioning
confidence: 99%
“…In the fluorophore-quencher pair, upon target binding, the ability of quencher to act upon the fluorophore reduces; however, in case of FRET pairs, the conformational change in the aptamer alters the distance between the fluorophore pairs and further alters the energy transfer in between them. This results in the shift of fluorescence emission from one fluorophore to the other and thereby change in the fluorescence color . The first assay using MABs was done to detect the Tat protein of HIV-1.…”
Section: Conclusion: Future Outlook and Roadmapmentioning
confidence: 99%
“…Aptamers are typically a kind of short single‐stranded oligonucleotide (DNA or RNA) sequences with a length of about 25–80 bases that mimic monoclonal antibodies and can be artificially synthesized via a selection process named systematic evolution of ligands by exponential enrichment (SELEX) in vitro (Ni et al., 2021). Although aptamers are commonly recognized as “chemical antibody” or “the fourth‐generation antibody,” compared to antibodies, they not only possess high binding affinity and specificity, but also demonstrate superiority of convenient generation, easy modification, good stability, low manufacturing cost, nontoxicity, little batch‐to‐batch differences, reversible folding features, nonimmunogenicity, and wide range of targets including small molecules, peptides, proteins, cells, and tissues (Ni et al., 2021; Zon, 2020). As a highly selective biological recognition element, aptamers have attracted considerable interest for constructing various types of aptasensors, displaying remarkable advantages related to high specificity and outstanding sensitivity, low cost, small consumption of reagents and samples, simplicity, and high‐throughput analysis (Cheng, Liu, et al., 2020; Yi et al., 2020; Zhang, Fan, et al., 2020).…”
Section: Introductionmentioning
confidence: 99%